Effect of Spring Buffer on Vehicle Dynamic Performance - Muhammad Khairul Najmi; Syabillah Sulaiman; Muhamad Asri Azizul (Progress in Engineering Application and Technology, 2024)
This study investigates at the impact of spring buffers on vehicle dynamic performance, specifically their role as energy-absorbing components in mechanical systems. The issue statement focuses the differences on impact and efficacy of buffer springs dependent on design characteristics such as stiffness, damping qualities, and preload. Road roughness, a critical factor affecting both driving comfort and safety, has been discovered as a significant component in the vibration of the connected system, further impacting the dynamic response of the vehicle. The study’s objectives include a thorough evaluation of the dynamic behaviour of buffer springs, the execution of tests to assess the dynamic impacts of different buffer springs, and a complete analysis of the effect of buffer springs on vehicle dynamic performance. The scope is confined to vehicle performance, primarily focused on the Perodua Myvi, and analysing just unsprung and sprung motion. The process entails creating a prototype with code and circuits, using Fritzing for offline tests and Arduino with MATLAB Simulink for online experimentation. Acceleration sensors (GY-61/ADXL335) are used, and trials are carried out at speeds of 10 km/h, 15 km/h, and 25 km/h on a standardised bump. The results, obtained through Arduino and MATLAB Simulink analysis, highlight the varying effects of buffer springs on both sprung and unsprung masses under different conditions and speeds, providing valuable insights for optimising buffer spring design and improving overall vehicle comfort, safety, and performance.